Re-imagining China’s future : soft power, cultural presence and the East Asian media market - Keane, Michael (Monash University ePress, 2010)
As various contributors to this volume suggest, the term soft power is multifaceted. In 2002 Joseph Nye, the political scientist who coined the term more than a decade previously, noted that the soft power of a country rests on three resources: a country’s culture, its political values, and its foreign policies (Nye 2002). However, several factors can be drawn together to explain China’s adoption of this concept. First, China’s economic influence has precipitated a groundswell of nationalism, which reached its apex at the Opening Ceremony of the 2008 Beijing Olympics. This global media event provided an international platform to demonstrate China’s new found self-confidence. Second, cultural diplomacy and foreign aid, particularly through Third World channels is seen by the Chinese Communist Party leadership as an appropriate way to extend Chinese influence globally (Kurlantzick 2007). Third, education in Chinese culture through globally dispersed Confucius Institutes is charged with improving international understanding of Chinese culture and values, and in the process renovating negative images of China. Fourth, the influence of Japanese and Korean popular culture on China’s youth cultures in recent years has caused acute discomfit to cultural nationalists. Many contend it is time to stem the tide. Fifth, the past few years have witnessed a series of lively debates about the importance of industries such as design, advertising, animation and fashion, resulting in the construction of hundreds of creative clusters, animation centres, film backlots, cultural precincts, design centres and artist lofts.